2013
DOI: 10.1177/1040638713504755
|View full text |Cite
|
Sign up to set email alerts
|

A survey of fish viruses isolated from wild marine fishes from the coastal waters of southern Korea

Abstract: Abstract.A survey was conducted to investigate viral infection in 253 wild marine fishes harvested in the southern coastal area of Korea from 2010 to 2012. The fish that were captured by local anglers were randomly bought and sampled for virus examination. The samples were tested for presence of virus by virus isolation with FHM, FSP, and BF-2 cells and molecular methods (polymerase chain reaction and sequencing). Of the 253 fish sampled, 9 fish were infected with virus. Aquabirnaviruses (ABVs), Viral hemorrha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…On the other hand, previous surveys of these viruses focused on different fish species in wild populations have been aimed mostly at fish of the orders Pleuronectiformes (flatfish), Clupeiformes (mainly herring and sprat), and Gadiformes (15,16,18,19,21,27,28,29,30) and to a lesser extent Perciformes (17,20,23,28,29). Most of these surveys employed isolation in cell culture for detection of carrier fish and reported very low prevalence values, which agrees with our results obtained with that procedure.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…On the other hand, previous surveys of these viruses focused on different fish species in wild populations have been aimed mostly at fish of the orders Pleuronectiformes (flatfish), Clupeiformes (mainly herring and sprat), and Gadiformes (15,16,18,19,21,27,28,29,30) and to a lesser extent Perciformes (17,20,23,28,29). Most of these surveys employed isolation in cell culture for detection of carrier fish and reported very low prevalence values, which agrees with our results obtained with that procedure.…”
Section: Discussionsupporting
confidence: 82%
“…The first remarkable result obtained in this study was that the three viruses were detected in the wild fish populations screened both near and far from the coast, although the detection percentages varied according to the fish species sampled, the season, and the geographical locations of the sampling areas. In fact, these results are not surprising at all, considering that the ubiquity of these three viruses in wild fish has been previously established in several surveys (14,15,16,17,18,19,20,21,22,23,24). In most cases, the wild fish sampled in those surveys were asymptomatic, although several outbreaks with pathological signs of VNNV infection and detection of the virus in wild fish have been recorded in Europe, near the coasts of Portugal and Italy (11,25,26).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The fish invitrome is widely used in developing antiviral strategies and comprehending the interaction between virus and the cells of hosts (Jia et al, ; Le et al, ; Zhang et al, ) and non‐hosts (Pham, Lai, Lee, Bols, & Chiou, ). Kim and colleagues reported that VHSV was detected in wild silver pomfret in Korea, indicating silver pomfret was the natural host of VHSV (Kim, Choi, Kim, & Oh, ). However, as yet, no cell lines from silver pomfret had been established, specially the cell line susceptible to VHSV.…”
Section: Introductionmentioning
confidence: 99%
“…() with degenerate primers for all four major genotypes. The protocols involve problems of sensitivity or specificity despite that those have been used in many laboratories including the World Organization for Animal Health (OIE) (Gomez et al., ; Kim, Choi, Kim, & Oh, ; OIE ). In terms of that, OIE has suggested to do further validation of the various PCR methods using more samples of naturally infected types to estimate the diagnostic sensitivity and specificity of the methods (OIE ).…”
Section: Introductionmentioning
confidence: 99%